Post-Covid cities and mobility: A proposal for an antifragile strategy in Rome - Ravagnan, Chiara; Cerasoli, Mario; Amato, Chiara (TeMA - Journal of Land Use, Mobility and Environment, 2022)
Mobility is considered a central topic for urban regeneration in metropolitan cities, in relation to the impact on traffic congestion, air pollution, public space quality, social inclusion. During the Covid-19 pandemic, mobility patterns have been strongly affected by the spread of the virus and the social distancing measures. In the last months, many cities have adopted mobility strategies for urban resilience, to face the crisis by the reorganization of infrastructures and networks with a glance at a prevention of an unsustainable return to private transport in the post-covid phase. In this context, the research illustrated in this paper, developed within a collaboration between Sapienza University of Rome and Roma Tre University, aims to propose an "anti-fragile" strategy for “post covid Rome”, adaptable to other contexts of European cities, starting from an integrated approach to urban planning and mobility. The research methodology has articulated the activities into three phases. The phase of analysis of the phenomena and the main scientific references relating to urban resilience and antifragility, highlighting the the relationship between urban form and mobility models. The second phase relates to the study of the main ongoing strategies and practices in some European metropolitan cities. The third phase proposes an operational hypothesis of an antifragile strategy for Rome highlighting the relevance of mobility transition. In the conclusion, the paper defines guidelines for urban regeneration combining the results of the case studies and the experimentation.